ANALISIS FENOMENA ELEKTROHIDRODINAMIK MENGGUNAKAN PLASMA LUCUTAN KORONA DC POSITIF DENGAN KONFIGURASI ELEKTRODA MATA PAHAT DAN TITIK TENGAH-BIDANG PADA MINYAK KELAPA SAWIT - Charis Munajib; Asep Yoyo Wardaya; Zaenul Muhlisin; Isnain Gunadi (BERKALA FISIKA, 2022)
Research  has  been  carried  out  on  the  analysis  of  I-V  characteristic  curves  and electrohydrodynamic phenomena using palm oil with a positive DC corona discharge generator with Chisel Eye and Mid-Field electrode configurations. This study aimed to obtain the effect of several  variations  used  on  the  characteristic  curve  and  distribution  of  ion  winds  on electrohydrodynamic phenomena. This research was conducted with 6 variations of the size of the dimensions of active electrodes and variations in the distance between the electrodes (c) 0.5 cm, 1 cm, 1.5 cm, and 2 cm. In the study of the I-V characteristic curve, the results show that with the increase in the applied voltage, the stronger the current produced will increase. At electrode D and a distance of 0.5 cm, the circuit is given a voltage of 5.32 kV produces a current of 10.5 A, whereas if the circuit is given a voltage of 6.34 kV it produces a current of 27.5 A. In the study of the analysis of electrohydrodynamic phenomena, it was found that if the variation used changed it would affect the diameter of the deformation of the palm oil in the form of a circle. At electrode D, at a distance of 0.5 cm with a voltage of 7.14 kV it produces a circular oil deformation diameter of  2.7  cm,  while  at  a  distance  of  1  cm  with  a  voltage  of  11.23  kV  produces  a  circular  oil deformation diameter of 5.5 cm.